2017
DOI: 10.1111/1753-0407.12624
|View full text |Cite
|
Sign up to set email alerts
|

How does CKD affect HbA1c?

Abstract: A number of factors determine HbA1c other than the level of glucose exposure alone. 1 In an subset analysis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Several reports have suggested that alteration of HbA1c levels can be affected by several common factors, including erythrocyte turnover, iron deficiency, and kidney failure (27)(28)(29). In the present study, the negative association was maintained after making allowance for all possible confounders.…”
Section: Discussionsupporting
confidence: 62%
“…Several reports have suggested that alteration of HbA1c levels can be affected by several common factors, including erythrocyte turnover, iron deficiency, and kidney failure (27)(28)(29). In the present study, the negative association was maintained after making allowance for all possible confounders.…”
Section: Discussionsupporting
confidence: 62%
“…≥65 years or with a Charlson comorbidity index scores ≥5 were excluded (Charlson et al, 1987;Bannay et al, 2016), considering that less stringent HbA1C goals (such as 8-8.5%) have been recommended for patients with limited life expectancy, extensive comorbid conditions, or frail, older adults since late 2000s (American Diabetes Association, 2021;American Diabetes Association, 2021). Patients with estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2 were also excluded as this may have affected the HbA1c level and not accurately reflect the true glycemic status (Bloomgarden & Handelsman, 2018). In the end, 4282 eligible patients with ≥ 1 year of analytical data were included ( Fig.…”
Section: Subjectsmentioning
confidence: 99%
“…Two reasons might explain this phenomenon. First, with the deterioration of renal function, the correlation between HbA1c and FPG is weakened, which is more obvious in patients with anemia [29]. HbA1c cannot accurately re ect recent blood glucose control in such situation.…”
Section: Discussionmentioning
confidence: 99%